Performance of a new recuperative Heat and Moisture Exchange Mask - Mario P. Wehrle; Thomas Küpper; Claus-M. Muth (University of Applied Sciences in Tarnow, Poland, 2021)
Aim of the study: The purpose of this work is to show the possibility to use a recuperative design of a heat and moisture exchange face mask (HME). Such HME are used as cold weather face masks for Arctic expeditions and conditioning of air for long-term intubated patients. Common regenerative HME have the disadvantage of increasing airway resistance and airway volume (dead space). In recuperative devices, the separation of inspired and expired airflow could reduce dead space and resistance. Materials and methods: Prototype HMEs were built using two concentric ducts of aluminium or cotton. A valve ensures that expired and inspired air are led through either the inner or the outer tube. The inner tube's wall transmits heat and water. The HMEs were tested in a simulated Arctic environment using a breathing simulator and characterized in terms of heat and moisture exchange efficiency. The new design was also tested at room temperature in order to simulate the conditions of long-term intubation. To compare the results, the relative difference in temperature (Performance Coefficient PC) between the expired and the inspired air was calculated. Results: During the experiments, the ambient temperature was −37°C and therefore the absolute water content was about zero. The recuperative HME conditioned the air to 21°C and 10.7 mg/l water (61% relative humidity), giving a PC of 82%. At room temperature the recuperative mask showed a PC of 62%. Conclusion: The recuperative HME shows great potential. It might be of use in clinical conditions and Arctic expeditions.